Effect of five selected flavonoids on the stability of anthocyanins: Kinetics, structural characterization, and interactional characteristics - Yini Fu; Yafei Dong; Jifang Miao; Xiaojuan Fan; DanDan Li; Yixuan Chen; Xingqian Ye; Yanyun Zhu (Food Chemistry, 2026)

Characterization of wheat starch–safflower seed oil complex and its effects on noodle quality and starch digestibility - Xiaochun Zheng; Xiaoxiao Liu; Jing Wang; Yini Fu; Meina Cheng; Li Tai; Xinwen Xu; Laizhong Wang; Yi Zhao; Min Liu; Wenyu Liu; Changqing Wei (Food Chemistry, 2026)

Transcriptome and Metabolome Profiling of Different Genotypes and Growth Stages in Stem Lettuce Reveals Changes in Terpenoid Components - Haiwang Zhang; Xueke Tian; Yini Fu; Xiaoqiang Wei; Qiwen Zhong; Shipeng Yang; Xuemei Sun; Lihui Wang (Plant Molecular Biology Reporter, 2026)

Green extraction of anthocyanins from Chinese bayberry (Myrica rubra Sieb. Et Zucc.) using acidic deep eutectic solvents: Enhancing the physicochemical properties and stability of anthocyanins. - Yini Fu; Yunyun Zheng; Baozhu Shi; Bingge Liu; Ming Zhang; Yanyun Zhu (Food Research International, 2025)

Soy isoflavones attenuate atrazine-induced neuroinflammation and dopaminergic neurotoxicity in the substantia nigra: Insights from the gut microbiota-LPS-TLR4/MyD88/NF-κB axis - Yinan Zhang; Yanming Lv; Yini Wang; Wenhao Fu; Xin-yu Shi; Jiaqi Liu; Jie Wen; Xueting Li; Baixiang Li (Food Bioscience, 2025)

Photochemical transformation of benzalkonium chloride in seawater - Quan Lin; Xiaokun Fu; Wenhao Jia; Guining Lu; Xingcai Chen; Kaibo Huang; Xueqing Zhou; Yini Ma (Journal of Hazardous Materials, 2025)

Effect on heat treatment on the physical stability, interfacial tension and in vitro digestion of whey protein-stabilized ω-6/ω-3 fatty acid balanced pumpkin seed oil complex condensate - Yini Fu; Jing Wang; Xiaoxiao Liu; Yongqing Ni; Zhiya Niu; Ligong Qiu; Zhanxia Liu; Changqing Wei (Food Hydrocolloids, 2025)

Carbon sequestration potential and its main drivers in soils under alfalfa (Medicago sativa L.) - Yi Xu; Xun Duan; Yini Wu; Huarong Huang; Tongcheng Fu; Houkun Chu; Shuai Xue (Science of The Total Environment, 2024)

The efficiency and stability of soil organic carbon sequestration by perennial energy crops cultivation on marginal land depended on root traits - Yi Xu; Xun Duan; Yini Wu; Tongcheng Fu; Wei Hou; Shuai Xue; Zili Yi (Soil and Tillage Research, 2024)

The GZnC1 variant from common wild rice influences grain Zn content - Jingjing Hou; Hao Chen; Kun Zhang; Wenjing Liu; Caihong Cao; Yini Ruan; Yanyan Deng; Yaxin Liu; Xuzhao Yuan; Chuanqing Sun; Yongcai Fu (Plant Molecular Biology, 2023)

Effects of Plant Growth Regulators, Soil Moisture Contents, and Carbon/Nitrogen Ratios on Sex Differentiation in Persimmon (Diospyros kaki Thunb.) Flowers - Liyuan Wang; Huawei Li; Peng Sun; Yujing Suo; Weijuan Han; Songfeng Diao; Yini Mai; Fangdong Li; Jianmin Fu (Journal of Plant Growth Regulation, 2021)

Development of EST-SSR markers and their application in the genetic diversity of persimmon (Diospyros kaki Thunb.) - Liyuan Wang; Huawei Li; Yujing Suo; Weijuan Han; Songfeng Diao; Yini Mai; Peng Sun; Jianmin Fu (Trees, 2021)

Selection and validation of reference genes for quantitative gene expression analyses in persimmon (Diospyros kaki Thunb.) using real-time quantitative PCR - Gaigai Du; Liyuan Wang; Huawei Li; Peng Sun; Jianmin Fu; Yujing Suo; Weijuan Han; Songfeng Diao; Yini Mai; Fangdong Li (Biologia Futura, 2020)
Background and aims Persimmon ( Diospyros kaki ) is an economically important fruit tree species with complex flowering characteristics. To obtain accurate expression pattern analysis results, it is vital to select a reliable gene for the normalization of real-time quantitative polymerase chain reaction data. The aim of this study was to identify the optimal internal control gene among six candidate genes for gene expression analysis in different persimmon organs and developmental stages. Materials and methods This analysis was conducted using geNorm and NormFinder software to show differences in the stability of the six reference genes among tissues and floral developmental stages of the same plant. Results Although genes that exhibited moderate expression in NormFinder revealed slightly different expression stabilities than those obtained by geNorm, both sets of results showed that GAPDH was the best reference gene in different organs and floral buds at different developmental stages, whereas 18SrRNA was the least stable gene. Conclusions Based on the overall ranking, GAPDH is the most suitable reference gene and is highly recommended for gene expression studies in different organs and different developmental stages of persimmon. This study provides useful reference data for future gene expression studies and will contribute to improving the accuracy of gene expression results in persimmon.